2011
DOI: 10.1038/npp.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Mineralocorticoid but not Glucocorticoid Receptors of the Dorsal Hippocampus Mediate the Rapid Effects of Corticosterone on Memory Retrieval

Abstract: This study was aimed at determining the type of the glucocorticoid membrane receptors (mineralocorticoid receptors (MRs) or glucocorticoid receptors (GRs)) in the dorsal hippocampus (dHPC) involved in the rapid effects of corticosterone or stress on memory retrieval. For that purpose, we synthesized corticosterone–3-O-carboxymethyloxime–bovine serum albumin conjugate (Cort–3CMO–BSA) conjugate (a high MW complex that cannot cross the cell membrane) totally devoid of free corticosterone, stable in physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Further, 50 mg spironolactone versus placebo for 6 weeks in obese individuals improved a hippocampal-dependant task-associate learning, which involves remembering that two previously unrelated items are associated with each other [56]. This result is consistent with preclinical studies suggesting that the hippocampal MR has a role in hippocampal memory modulation [57].…”
Section: Mr and The Cardiovascular And Renovascular Systems Insupporting
confidence: 75%
“…Further, 50 mg spironolactone versus placebo for 6 weeks in obese individuals improved a hippocampal-dependant task-associate learning, which involves remembering that two previously unrelated items are associated with each other [56]. This result is consistent with preclinical studies suggesting that the hippocampal MR has a role in hippocampal memory modulation [57].…”
Section: Mr and The Cardiovascular And Renovascular Systems Insupporting
confidence: 75%
“…Although the latter was found to be sensitive to G i/o inhibition (PTX) and to a general inhibitor of GPCR function (SCH20267), the nature of the putative membrane-localized CORT receptor remains unknown. Although some earlier studies observed immunoreactivity corresponding to the classical, nuclear GR in the plasma membrane (12,15,40,42), more recent ones have proposed that the fast actions of CORT in hippocampal neurons are mediated by translocated nuclear MR (7,43). It is pertinent to note that recent work has implicated an orphan GPCR in fast signaling by two other steroid hormones, estradiol and aldosterone (44,45); the latter is enzymatically (18-hydroxylase and 18-hydroxysteroid dehydrogenase) derived from CORT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vivo microdialysis is an extremely powerful method to study the highly dynamic neurotransmitter responses in the field of stress physiology and behavior (Linthorst and Reul, 2008; Dorey et al , 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The doses of antagonists were selected according to a previous study (Dorey et al , 2011). The antagonists were bilaterally injected 15 min before stress and 30 min before the test session.…”
Section: Figurementioning
confidence: 99%